2012
DOI: 10.1117/1.jei.21.4.043020
|View full text |Cite
|
Sign up to set email alerts
|

Wiener discrete cosine transform-based image filtering

Abstract: Abstract. A classical problem of additive white (spatially uncorrelated) Gaussian noise suppression in grayscale images is considered. The main attention is paid to discrete cosine transform (DCT)-based denoising, in particular, to image processing in blocks of a limited size. The efficiency of DCT-based image filtering with hard thresholding is studied for different sizes of overlapped blocks. A multiscale approach that aggregates the outputs of DCT filters having different overlapped block sizes is proposed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
1
43
0
4
Order By: Relevance
“…This potential output MSE considerably depends on image complexity and increases proportionally to noise variance, but not linearly (if noise variance increases twice, output MSE becomes larger by about 1.6 times for most images). This means that the most complicated task is to provide high efficiency of noise removal for complex-structure images if noise variance is not large (similar results and conclusions have been obtained in [7] where potential of image denoising is analyzed within Wiener and DCT filtering approach).…”
Section: Introductionsupporting
confidence: 75%
“…This potential output MSE considerably depends on image complexity and increases proportionally to noise variance, but not linearly (if noise variance increases twice, output MSE becomes larger by about 1.6 times for most images). This means that the most complicated task is to provide high efficiency of noise removal for complex-structure images if noise variance is not large (similar results and conclusions have been obtained in [7] where potential of image denoising is analyzed within Wiener and DCT filtering approach).…”
Section: Introductionsupporting
confidence: 75%
“…The following procedure has been proposed in Ref. 26. The initial step 1 is to skip¯ltering if P 0:5 < 0:25.…”
Section: New Solutions For Prediction Of Denoising E±ciency Indicatorsmentioning
confidence: 99%
“…50 Recently, the powerful clustering-based denoising schemes have been proposed: KSVD 43 and KLLD 3 that use learned dictionaries in di®erent ways, and a¯lter based on gradient histogram preservation (GHP). 54 Their analysis has shown that most of the aforementioned denoising techniques perform similarly (approximately at the same level as standard DCT-based¯lter 22,26 and BM3D¯lter 11 ) whilst NLM and LPG-PCĀ lters 4,6 perform su±ciently worse. Moreover, it is worth performing a more careful analysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations